PRAKTIKUM PELANGI SEBAGAI UPAYA PENGUATAN KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN IPA DI SEKOLAH ALAM ISLAMIC ORBIT SCHOOL ACEH BESAR - Eka Yulianti; Lili Kasmini; Siti Mayang Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the rainbow practicum as an effort to strengthen science process skills in Natural Science (IPA) learning at Sekolah Alam Islamic Orbit School Aceh Besar. Science process skills are essential in developing students’ scientific thinking, critical reasoning, and problem-solving abilities. This study employed a descriptive qualitative approach involving elementary school students learning the topic of light. Data were collected through observations of student activities during the practicum, learning documentation, and teachers’ reflective notes, and analyzed using data reduction, data display, and conclusion drawing. The findings show that the rainbow practicum effectively strengthens students’ science process skills, particularly in observing, classifying, interpreting data, and drawing conclusions. This nature-based practicum also increases students’ active participation and enthusiasm in learning. Furthermore, it helps students understand light concepts more concretely, fosters scientific attitudes, and connects science concepts to everyday phenomena. Therefore, the rainbow practicum is an effective and contextual alternative strategy for science learning in nature-based school environments.